Path Dependence from Proxy Agent to De Facto State: A History of ‘Strategic Exploitation’ of the Kurds as a Context of the Iraqi Kurdistan Security Policy - Sosnowski, Piotr (International Journal of Conflict and Violence (IJCV), 2022)
The scientific goal of this paper is to conceptualize the phenomenon of ‘strategic exploitation’ of Kurdish political entities and to investigate it as a process that triggered the change in Kurdish actorness from isolated non-state to de facto state. Covering two centuries, the contribution examines actorness and cases of patron-client relations between Kurdish political entities and sovereign states. It answers the question: What was the path of strategic exploitation of the Kurdish political entities and how does it affect the contemporary security policy of Iraqi Kurdistan? Combining the concepts of proxy war, de facto state, and path dependence, it argues that the persistent experience of strategic exploitation shaped the collective strategic thought of Kurdish political entities and has a visible impact on contemporary Iraqi Kurdistan security policy. It applies the process-tracing method based on an analysis of literature on the history of Kurds and Kurdistan to investigate patron-client relations and variability of actorness. The article concludes that the experience of ‘strategic exploitation’ has shaped the main direction of Iraqi Kurdistan security policy. It is expressed in practice as abstaining from an official declaration of secession and diversifying relations with external actors.